Haemato-oncological disease and inmigration: itineraries for exclusion? - Vázquez, Nika; Díaz, Laura; García, Helena; García, Paula; Barbero, Javier; Coca, Cristina (Psicooncología, 2008)
Health Services have to deal with new and frequent social phenomena of migratory flows. There are many factors related to the health/illness process among the immigrants, resulting sometimes in exclusion itineraries. The present study pretends to describe the psychosocial variables related to immigrant patients with a haematological disease in a specialized hos¬pitalization setting. We evaluated a sample of sixty immigrant patients’ hospitalized at the Haematology Service of the University Hospi tal La Paz. Most of them were women and the mean of age was 40 years old. A great number of these patients were from Latin-America. They were married, but without primary caregiver, although, they perceived family and social support. They presented economic difficulties and poor social-economic resources being most of them unemployed. Not significant levels of anxiety and/or depression were reported. Our study reflects a precarious scene for these patients when they face the double challenge of the immigration and the threat of the haematological disease. From the research we can take out concrete improvement proposals in order to reinforce our specific compromise against the suffering experience related to the disease and the exclusion experience. We realize that these kind of research helps to preserve the most disfavoured rights. We understand that this type of investigations helps to preserve the rights of the most disfavoured.